Classifying the Zhuangzi Chapters - Liu, Xiaogan (Michigan Monographs In Chinese Studies, 2020)
The relationships, both historical and philosophical, among the Zhuangzi's Inner, Outer, and Miscellaneous chapters are the subject of ancient and enduring controversy. Liu marshals linguistic, intertextual, intratextual, and historical evidence to establish an objectively demonstrable chronology and determine the philosophical affiliations among the various chapters. This major advance in Zhuangzi scholarship furnishes indispensable data for all students of the great Daoist text. In a lengthy afterword, Liu compares his conclusions with those of A. C. Graham and addresses the relationship between the Zhuangzi and the Laozi.